AN ACCOUNTING-BASED EVALUATION FRAMEWORK FOR DISASTER REPORTING IN DECENTRALIZED GOVERNANCE: INTEGRATING IPSASB QUALITATIVE CHARACTERISTICS, GRI REPORTING PRINCIPLES, AND INSTITUTIONAL THEORY - Gabriel P Aryanindita; Caecilia Atmini Susilandari (RADJA PUBLIKA, 2026)
Disaster reporting has become an essential instrument for strengthening public accountability in disaster risk management, yet its accounting quality remains underexplored. Existing studies have predominantly examined disaster governance from institutional, operational, or policy perspectives, with limited attention to whether disaster reports provide useful, transparent, and stakeholder-oriented information in accordance with internationally recognised reporting principles. This study addresses this gap by developing and applying an integrated accounting-based evaluation framework that combines the International Public Sector Accounting Standards Board (IPSASB) qualitative characteristics of useful public-sector information with the Global Reporting Initiative (GRI) reporting principles. Institutional Theory is adopted as the theoretical lens to explain how regulatory, professional, and organisational pressures influence reporting practices within Indonesia's decentralized disaster governance system. A qualitative multiple-case study design was employed using directed qualitative content analysis of sixteen official disaster management reports issued by the National Disaster Management Agency (BNPB), Provincial Disaster Management Agencies (BPBDs), and provincial governments. The analysis evaluates disaster reporting against six IPSASB qualitative characteristics—relevance, faithful representation, comparability, verifiability, timeliness, and understandability—and four GRI reporting principles—materiality, completeness, stakeholder inclusiveness, and balance. The findings reveal that Indonesia's disaster reporting system demonstrates strong financial accountability and regulatory compliance but remains fragmented across multiple reporting instruments. While financial disclosures generally satisfy IPSASB qualitative characteristics, reporting on stakeholder engagement, methodological transparency, organisational learning, and long-term recovery outcomes remains comparatively limited. The study contributes to public sector accounting by extending the application of IPSASB qualitative characteristics beyond financial reporting and integrating them with GRI reporting principles to evaluate disaster reporting as a multidimensional accountability mechanism. The proposed framework offers a transferable approach for improving transparency, comparability, and public accountability in disaster reporting across decentralized governance systems.